Genetic epidemiology of epithelial-stromal TGFBI dystrophies in a large Korean population - Eun Hye Cho; Myoungkeun Lee; Chang-Seok Ki; Chang Ahn Seol; Mi-Ae Jang (Scientific Reports)
Abstract Epithelial-stromal TGFBI dystrophies are a group of inherited corneal disorders associated with variants in the TGFBI. This study investigated the allele frequency of major TGFBI variants and estimated the prevalence of epithelial-stromal TGFBI dystrophies in a large Korean population. Genetic analysis was performed on 129,933 individuals who underwent health checkups between July 2021 and August 2024. The presence of six major variants, R124L, R555Q, R124C, P501T, R555W, and R124H, was analyzed using next-generation sequencing. Three variants were detected in this study: R124H, P501T, and R555W, with allele frequencies of 0.10%, 0.58%, and 0.001%, respectively. The prevalence estimates for granular corneal dystrophy type 2, lattice corneal dystrophy variant, and granular corneal dystrophy type 1 were 203.9, 1160.3, and 2.3 per 100,000, respectively. The collective prevalence estimate of epithelial-stromal TGFBI dystrophies was 1365.2 per 100,000. This study provides a comprehensive analysis of TGFBI variants in a large homogenous Korean population and offers valuable insights into the genetic epidemiology of epithelial-stromal TGFBI dystrophies in South Korea. These findings contribute to a better understanding of the genetic prevalence of epithelial-stromal TGFBI dystrophies in the Korean population.